Humanising and harmonising Africans through Poetry: the Chirikure Chirikure example - Tembo, Charles (Midlands State University, 2016)
Tapping from Chirikureís poetry anthologies, this paper is a conscious engagement with Chirikure's contribution to humanization and harmonization of African people. It is stressed in this paper that Chirikure is a leading figure in repudiating existential nihilism. It is argued here that Chirikureís of erings reveal relentless commitment to ësetting afootí new men and women who are subjects and not objects. Against this background, it is also observed in the paper that while Chirikure is able to see the indispensability of Afrocentric action for liberation and progress, he seems to "blame the victim for a crime" Achebe (2009) instead of the systems that are responsible for objectifying Africans. The paper is couched in and guided by Afrocentricity.